Gender Equality in Indonesian Democracy amidst Islamic Conservatism and Islamic Populism - Qodir, Zuly; Misran, Misran; Long, Ahmad Sunawari (JSW (Jurnal Sosiologi Walisongo), 2023)
The growth of democracy in Indonesia from 1999 to 2019 was significantly hampered by Islamic populist forces, conservatives, and politicians who discriminated against women. This article aims to explore the challenges facing Indonesian political democracy after the 2014 and 2019 elections, using qualitative methods and interviews with party officials. The study uses the theories of Islamic populism, conservation, and discrimination against women. The article finds that the most dangerous challenges include the presence of populist and conservative Islamic forces that use religious sentiment in elections, political party elites that use women as men's political friends, and women seen as a threat to male politicians. This article emphasizes the importance of considering factors outside the electoral political process, such as religious beliefs and understanding, especially in the Indonesian context.